Análise da influência dos reservatórios de detenção domiciliares no escoamento superficial urbano - Francischet, Marcelo Martinelli (2012)
The home detention reservoirs for temporary storage of rain water have been proposed as a new control measure discharges in urban runoff. This work studied the effect of implementing these reservoirs damping in a neighborhood of the city of Uberlândia (MG), located in the Córrego da Lagoinha basin with the scenario of urbanization through hydrological simulation program developed in Visual Basic for Applications (VBA). Were designed and used home three reservoirs: the first and largest, has been designed with full insertion of the precipitation to rain initial return period of 10 years and tested for rain maximum design of 100 and 200 years, having a damping volume to 5.015 m3, while the other two were rated partial insertion of precipitation, by using a box server, to a rain initial return period of 05 years and tested for maximum rains design of 100 and 20 years, respectively where their damping volumes were 3.25 and 1.50 m3. The results for the three reservoirs hydrologic simulation showed that the attenuation of the peak flows to their maximum rains, the efficiencies were 32.23%, 24.27% and 15.47% for the reservoirs 5.015 m3, 3.25 m3 e 1.50 m3, respectively, and delayed the peak time of 50.81%, 34.0% and 19.61%.